Topological Properties of Nanostar Dendrimer and Smart Polymer - Muhammad Aamer Rashid; Sarfraz Ahmad; Murat Cancan; Mehwish Hussain Muhammad (Journal of Chemistry)
The nanostar dendrimers are a piece of another gathering of macromolecules that seem, by all accounts, to be photon pipes simply like counterfeit reception apparatuses. In addition, nanostar dendrimers are one of the fundamental stuffs of nanobiotechnology. The smart polymers are large-scale particles that show an emotional physioconcoction change because of little changes in their condition, for example, temperature, pH, light, attractive field, and ionic variables. A topological record of a graph G is a numeric quantity notorious with G which portrays subatomic diagram G. In this paper, we decide first and second Zagreb indices, hyper-Zagreb index, first multiple Zagreb index, second numerous Zagreb index, and Zagreb polynomials for nanostar dendrimer and smart polymer.